HIGH-FREQUENCY RADAR FOR COASTAL AREAS MONITORING - V. I. Veremyev; V. M. Kutuzov; K. S. Plotnitskaya; V. V. Kovalenko; V. A. Telegin (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The modern approach for ensuring marine activities of necessary quality related to the assessment of current information on the state of the ocean environment in Russia is clearly insufficient. The development of operational methods and instruments of observation, as well as the assessment of the state of the ocean and its forecast naturally determine such an approach. Therefore, the development of the concept, tools and methods of obtaining data is an urgent task of the operational Oceanography formation.Objective. The objective of the paper is to con-sider the concept of ocean surface monitoring using short-wave surface wave radar.Methods and materials. The paper presents a number of specific Oceanologic examples that require operational monitoring of the state of coastal waters of the oceans and individual regions. Also, it describes observational systems used in other countries. The paper pays special attention for the development of radar sensing of surface waters, carried out in our country occasionally. The resonant nature of the reflections gives the opportunity to obtain maps of high-precision measurements of surface currents and wave characteristics on the long-range area in real time. The paper notes difficulties of the experiments implementation and the results interpretation, shows the insistent issues for the establishment of the ocean surface operational monitoring, and gives the approaches for solvation of the existing problems. The paper formulates the main task of the world ocean parameters forecast for ensuring of the sea transport safety from natural and anthropogenic threats, as well as formulates the problems solution of effective nature management.Results. The paper shows that the optimal means of natural data acquisition is the creation of an observation network of coastal HF radars, which enables to assess surface currents and wave characteristics, as well as to solve the problem of monitoring. It is Important to develop an adequate coastal model and correlate its parameters with experimental data. The adaptive modeling and monitoring by modern technical means can overcome inadequacy of physical models to specific natural conditions can.Conclusion. By assimilation in hydrodynamic and wave models, these data become applicable in spatial mapping of hydrophysical inhomogeneities of the water layer, sound velocity, and underwater acoustic noise.